Optimasi Metode Kerja Terhadap Biaya dan Waktu Pada Pekerjaan Peningkatan Struktur Jalan - Luthfi Naufal; Muhammad Ridha; Amalia Effendy (Center for Research and Community Service (LPPM) University of Abulyatama, 2021)
In the 2017 fiscal year, one of the roads that will be enhanced with service capabilities and comfort is the work package for the improvement of the Sawah Block - Blang Paseh road in Sigli City. This work was carried out for 150 days with a contract value of Rp. 8,286,227,000.00, - (eight billion two hundred eighty-six million two hundred and twenty-seven thousand rupiah) with a road length of 1023 meters and a width of 8 meters. The job is delayed in time, this has an impact on the cost of the job. Therefore, the calculation of the optimization of the work method is carried out on the cost and time required to complete the usual pile work from the excavation source, selected embankments from the excavation source, road body preparation, class B aggregate foundation layer, and class A aggregate foundation layer. method of work, namely method 1 is to do the job thoroughly until it is finished then proceed to the next job, and method 2 is to do the work per item to completion by increasing the capacity of the tool. When calculated using method 1, this work can be done for 21 days at a cost of Rp. 306,800,000.00, - and using method 2 for 11 days at a cost of Rp. 324,500,000.00, -. Method 1 can be said to be more optimal than method 2 because it costs less, even though the time used is longer than method 2.